Seaweed (Hypnea SP.) Supplementation in Feed Play Role in Boosting Immunity of Nile Tilapia (Oreochromis Niloticus) (Dhaka University Journal of Biological Sciences, 2022)
Hypneasp. is the most common economically potential seaweed species inBangladesh. In this experiment, an initiative was taken to formulate fish feedusing seaweed (Hypneasp.) that can improve the immunity of Nile Tilapia,Oreochromisniloticus. Seaweed was supplemented in different percentages withcommercial feed to evaluate their effects on their serum bactericidal activities. A90-days experiment was conducted under five treatments – T1 (5% seaweed), T2(10% seaweed), T3 (15% seaweed), T4 (20% seaweed) and C (only commercialfeed) with a replica for each. Fish blood was collected, serum was separated fromblood and serum bactericidal activity was tested. Blood serum of 10% seaweedtreated fish showed the highest sensitivity against three bacteria (Bacillus cereus,Salmonella typhimurium, Shigellaflexneri) followed by 5% seaweed which showedsensitivity against Bacillus cereus and slightly against Salmonella typhimuriumandShigellaflexneriand 15% seaweed showed slight bactericidal activity againstBacillus cereus only, whereas, no bactericidal activity was observed for controland 20% seaweed treated fishes. The result indicates that the use of an optimumamount of seaweed supplements can improve the immunity system of Niletilapia which can prevent the growth of bacteria and likely make fishes safe forhuman consumption.Dhaka Univ. J. Biol. Sci. 31(1): 177-181, 2022 (January)